2018
DOI: 10.1002/marc.201800282
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Responsive and Thermoresponsive Supramolecular Nanosheet Gels with High Young's Moduli

Abstract: Supramolecular gels made from 2D building blocks are emerging as one of the novel multifunctional soft materials for various applications. This study reports on a class of supramolecular nanosheet gels formed through a reversible self-assembly process involving both intramolecular folding and intermolecular self-assembly of poly[oligo(ethylene glycol)-co-(phenyl-capped bithiophenes)]. Such hierarchical self-assembled structure allows the gels to switch between sol and gel states under either redox or thermosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Synthesis of Compound 15. Imidazole-1-sulfonyl azide hydrogen sulfate (14•H 2 SO 4 , 647 mg, 2.39 mmol) was added to a mixture of the commercially available N 1 ,N 4 ,N 9 -tris(Boc)spermine (1.0 g, 1.99 mmol), K 2 CO 3 (0.5 mmol), and CuSO 4 •5H 2 O (5 mg, 0.02 mmol) in methanol (22 mL), and the resulting reaction mixture was stirred at r.t. for 30 h. It was diluted with H 2 O (50 mL) and extracted with ethyl acetate (3 × 50 mL). After drying the organic layer over anhydrous Na 2 SO 4 , the volatiles were removed under reduced pressure.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of Compound 15. Imidazole-1-sulfonyl azide hydrogen sulfate (14•H 2 SO 4 , 647 mg, 2.39 mmol) was added to a mixture of the commercially available N 1 ,N 4 ,N 9 -tris(Boc)spermine (1.0 g, 1.99 mmol), K 2 CO 3 (0.5 mmol), and CuSO 4 •5H 2 O (5 mg, 0.02 mmol) in methanol (22 mL), and the resulting reaction mixture was stirred at r.t. for 30 h. It was diluted with H 2 O (50 mL) and extracted with ethyl acetate (3 × 50 mL). After drying the organic layer over anhydrous Na 2 SO 4 , the volatiles were removed under reduced pressure.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Despite being predominantly comprised of liquids, the resulting gels display solidlike mechanical properties in their rheological behavior . Importantly, in general, molecular organo- and hydrogels offer reversible control of their mechanical properties when perturbed by external stimuli, such as temperature, light, electric field, pH, oxidation–reduction, or mechanical stress . The reversible mechanical properties are consequences of the structural reorganization of gelators .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these materials showed temperature‐dependent mechanical properties, even undergoing sol–gel transitions. These kinds of materials that can be reversibly formed, offer a unique versatility for several applications in the biomedical field …”
Section: Viscoelastic Thermal and Water Swelling Characteristics Ofmentioning
confidence: 99%
“…Nakahata et al demonstrated a redox-responsive gel based on the different interactions of ferrocene to β-cyclodextrin and styrenesulfonic acid sodium salt under oxidative and reductive conditions . Although these studies were valuable, however, most of the changes resulted from redox stimuli in supramolecular gels are phase transitions, , color or mechanical properties, , and few studies have examined redox-responsive gel with the switch of luminescence. Obviously, luminescence based on intramolecular energy transitions are more sensitive and convenient to detect.…”
Section: Introductionmentioning
confidence: 99%